Problematika Kesehatan Mental Remaja di Kota Mataram Provinsi Nusa Tenggara Barat - Pujiarohman, Pujiarohman; Syamsun, Arfi; Harahap, Ida Lestari; Herlina, Lenny; Wahid, Lalu Abdurrachman (YASIN, 2025)
This study aims to explore the factors influencing adolescent mental health in Kota Mataram, focusing on access to mental health services and the influence of local culture, as well as evaluating the effectiveness of intervention programs such as school-based mental health initiatives and community awareness campaigns tailored to adolescent needs. A qualitative approach with descriptive analysis was employed. Data were collected through Focus Group Discussions (FGDs) involving health cadres from community health centers (puskesmas), members of the Child Protection Agency (Lembaga Perlindungan Anak or LPA), and the Kota Mataram Children’s Council Team (Tim Dewan Anak). The study is grounded in the urgency of mental health as an integral component of adolescent development and seeks to present a comprehensive overview of causal factors, access barriers, and efforts undertaken by local stakeholders. In addition to identifying risk factors, the research examines contextually relevant intervention strategies to support adolescent mental health. Data analysis was conducted using Constant Comparative Data Analysis, which includes data reduction, presentation, and verification, applying both deductive and inductive approaches simultaneously to produce valid and in-depth results. The findings are expected to contribute meaningfully to the development of responsive mental health policies in Kota Mataram and to support the implementation of adaptive intervention programs in educational and community settings.